1976
DOI: 10.1093/jn/106.1.86
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Essential Role for Dietary Linolenic Acid in the Development of the Young Rat

Abstract: Female rats were fed semi-purified diets containing 10% safflower oil or 10% soybean oil for six weeks prior to mating and through-out pregnancy and lactation. The progeny were weaned to the diet of the dam. Physical, neuromotor and reflex development was monitored in the progeny prior to weaning and learning ability of the mature progeny was assessed in a simple Y-maze test. Brain lipid analyses were conducted in the progeny at birth, 21 and 210 days of age. Inclusion of soybean oil in the diet resulted in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
2
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(126 citation statements)
references
References 22 publications
5
117
2
2
Order By: Relevance
“…On the other hand, the addition of linoleic acid or its metabolic products, such as arachidonic acid or prostaglandin E 2 , to the EFAD diet have been shown to prevent impairment of the reproductive function (Burr and Burr, 1930 ;AlfinSlater et al, 1965 ;Tinoco et al, 1971 ;Hafiez, 1974 (Turpeinen, 1938 ;Panos and Finerty, 1953 Rivers, 1978 ;Rivers and Frankel, 1981 ;Tinoco, 1982) and, to our knowledge, there is no bibliographical evidence suggesting that n-3 fatty acids are required to maintain a normal pattern of estrous cycles. However, changes in other physiological functions have been observed in animals selectively deprived of n-3 fatty acids for prolonged periods (Castell et al, 1972 ;Benolken, Anderson and Wheeler, 1973 ;Lamptey and Walker, 1976 (Alling et al, 1972). In contrast with other authors (Evans, Lepkovsky and Murphy, 1934 ;Kummerow, Pan and Hickman, 1952), we found that sterility and maternal mortality during parturition were not significantly different among the three groups.…”
contrasting
confidence: 99%
“…On the other hand, the addition of linoleic acid or its metabolic products, such as arachidonic acid or prostaglandin E 2 , to the EFAD diet have been shown to prevent impairment of the reproductive function (Burr and Burr, 1930 ;AlfinSlater et al, 1965 ;Tinoco et al, 1971 ;Hafiez, 1974 (Turpeinen, 1938 ;Panos and Finerty, 1953 Rivers, 1978 ;Rivers and Frankel, 1981 ;Tinoco, 1982) and, to our knowledge, there is no bibliographical evidence suggesting that n-3 fatty acids are required to maintain a normal pattern of estrous cycles. However, changes in other physiological functions have been observed in animals selectively deprived of n-3 fatty acids for prolonged periods (Castell et al, 1972 ;Benolken, Anderson and Wheeler, 1973 ;Lamptey and Walker, 1976 (Alling et al, 1972). In contrast with other authors (Evans, Lepkovsky and Murphy, 1934 ;Kummerow, Pan and Hickman, 1952), we found that sterility and maternal mortality during parturition were not significantly different among the three groups.…”
contrasting
confidence: 99%
“…Representative studies in the animal literature (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) concerning the n-3 fatty acid deficiency syndrome are presented in Table 2. Only studies that focus on neural functions, notably brain and retinal functions, have been included here.…”
Section: Animal Studiesmentioning
confidence: 99%
“…24 For example, docosahexanoic acid (C22:6 co-3) appears to play a role in the proper functioning of nervous tissues, 25 and impaired maze-running abilities have been found in co-3 fatty-acid-deficient rats. 26 Remarkably high levels of C22:6 co-3 are found in brain and retinal cells as well as in spermatozoa. 24 Although further studies will be required to document structural or metabolic defects resulting from dietary co-3 fatty acid deprivation, the presence of high levels of these unique acids in certain tissues and the known Inability of mammalian cells to synthesize these de novo imply a dietary requirement for co-3 fatty acids.…”
Section: Polyunsaturated Fatty Acid Families and Interrelationshipsmentioning
confidence: 99%